Microeconometric evidence on demand-side real rigidity and implications for monetary non-neutrality - Günter W. Beck; Sarah M. Lein (University of Basel, Center of Business and Economics (WWZ), 2015)
To model the observed slow response of aggregate real variables to nominal shocks, most macroeconomic models incorporate real rigidities in addition to nominal rigidities. One popular way of modelling such a real rigidity is to assume a non-constant demand elasticity. By using a homescan data set for three European countries, including prices and quantities bought for a large number of goods, in addition to consumer characteristics, we provide estimates of price elasticities of demand and on the degree of demand-side real rigidities. We find that price elasticities of demand are about 4 in the median. Furthermore, we find evidence for demand-side real rigidities. These are, however, much smaller than what is often assumed in macroeconomic models. The median estimate for demand-side real rigidity, the super-elasticity, is in a range between 1 and 2. To quantitatively assess the implications of our empirical estimates, we calibrate a menu-cost model with the estimated super-elasticity. We find that the degree of monetary non-neutrality doubles in the model including demand-side real rigidity, compared to the model with only nominal rigidity, suggesting a multiplier effect of around two. However, the model can explain only up to 6% of the monetary non-neutrality observed in the data, implying that additional multipliers are necessary to match the behavior of aggregate variables.
Keywords: E30; E31; E50; D12; C3; 330; Demand curve; price elasticity; super-elasticity; price-setting; monetary non-neutrality